Living biobank: Standardization of organoid construction and challenges - Ruixin Yang; Yao Qi; Xiaoyan Zhang; Hengjun Gao; Yingyan Yu; Yuanyuan Ji (Chinese Medical Journal)
Abstract. In multiple areas such as science, technology, and economic activities, it is necessary to unify the management of repetitive tasks or concepts by standardization to obtain the best order and high efficiency. Organoids, as living tissue models, have rapidly developed in the past decade. Organoids can be used repetitively for in vitro culture, cryopreservation, and recovery for further utilization. Because organoids can recapitulate the parental tissues’ morphological phenotypes, cell functions, biological behaviors, and genomic profiles, they are known as renewable “living biobanks”. Organoids cover two mainstream fields: Adult stem cell-derived organoids (also known as patient-derived organoids) and induced pluripotent stem cell-derived and/or embryonic stem cell-derived organoids. Given the increasing importance of organoids in the development of new drugs, standardized operation, and management in all steps of organoid construction is an important guarantee to ensure the high quality of products. In this review, we systematically introduce the standardization of organoid construction operation procedures, the standardization of laboratory construction, and available standardization documents related to organoid culture that have been published so far. We also proposed the challenges and prospects in this field.